4f-5d Transitions of Tb3+ in Cs2NaYF6: The Effect of Distortion of the Excited-State Configuration - Duan, C.K.; Tanner, P.A.; Meijerink, A.; Makhov, V. (American Chemical Society, 2011)
The low-temperature absorption and excitation spectra of interconfigurational 4f–5d transitions of Tb3+ in a cubic fluoride host demonstrate the appearance of a first-order linear Jahn–Teller effect for the high-spin excited states of the excited electronic configuration 4f75d involving 5d t2g orbitals. The τ2g mode is observed to be responsible for the splitting of the otherwise degenerate 5d t2g orbitals.